2020
DOI: 10.1007/978-3-030-50506-6_22
|View full text |Cite
|
Sign up to set email alerts
|

EDUGAME4CITY. A Gamification for Architecture Students. Viability Study Applied to Urban Design

Abstract: Hereby we present the first results of a Financed Research Project that focuses on the use of (Serious games) SG for training future architects and urban planner in the urban design context. After the first viability studies and tests in the creation of urban scenarios at intermediate scale, virtual simulation, vegetative environment and lighting, as well as basic gamification, the complete development of the teacher's methodology proposal of the research project is outlined. First five urban scenarios have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
(17 reference statements)
0
9
0
1
Order By: Relevance
“…The main aim of the current project is to show how the implementation of “gamified” virtual strategies in architecture and urban design can increase students’ spatial comprehension and citizens’ interest in the collaborative/gamified/interactive design of spaces. To address our objectives, we have identified four primary areas of action within the project ( Figure 1 ), namely, research, open innovation and entrepreneurship; improved education and awareness; and citizen participation [ 116 ]. Working within these four primary areas, we further identified six main actions that the project addresses, namely, education, architecture, citizenship, sustainability, territory and technology, at whose intersections we find the following five main components to develop: Art, science and technology: As we explained previously, we are developing interactive and gamified representations of urban spaces for specific proposals related to the final entities’ needs using new interactive platforms.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The main aim of the current project is to show how the implementation of “gamified” virtual strategies in architecture and urban design can increase students’ spatial comprehension and citizens’ interest in the collaborative/gamified/interactive design of spaces. To address our objectives, we have identified four primary areas of action within the project ( Figure 1 ), namely, research, open innovation and entrepreneurship; improved education and awareness; and citizen participation [ 116 ]. Working within these four primary areas, we further identified six main actions that the project addresses, namely, education, architecture, citizenship, sustainability, territory and technology, at whose intersections we find the following five main components to develop: Art, science and technology: As we explained previously, we are developing interactive and gamified representations of urban spaces for specific proposals related to the final entities’ needs using new interactive platforms.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In this paper, we present an immersive game (Game for Safety) that consists of a virtual environment endowed with signage and risks in which it is possible to extract user information and improve learning. This work born as an adaptation of the application created for the Game4City 3.0 project, which is being developed (2016–2021) by the Barcelona School of Architecture (Catalonia Polytechnic University, ETSAB-UPC) and the School of Architecture of La Salle—Ramon Llull University (ETSALS-URL) [ 34 , 35 , 36 ]. Game4City applies VR strategies to design 3D indoor and outdoor spaces for educational purposes [ 31 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is clear that the design of the activities and the urbanism of today’s cities requires the participation of all the actors involved. The Game4City project, which is the focus of this research, demonstrated in its previous iterations [ 105 , 106 , 107 , 108 , 109 ] that by visualizing and interacting with future designs, both citizens and the entities that promote them can make better decisions. Simulation with interactive virtual reality systems of specific areas for specific uses allows for the co-design of space and its functions, democratizing the cities of the future [ 105 , 110 ].…”
Section: Discussionmentioning
confidence: 99%